Cultural Adaptation of Psychological Therapies Delivered by Community Health Practitioners in Africa to Those Suffering from Mental Illnesses: A Scoping Review - Moses, Nsubuga (Happiness: Journal of Psychology and Islamic Science, 2025)
Community health professionals play a vital role in addressing gaps in mental health care access across African communities. However, limited evidence exists on their roles, the effectiveness of the psychological interventions they deliver, and the extent to which these interventions are culturally adapted. This scoping review aimed to examine the types, cultural adaptations, and sustainability of psychological therapies provided by community health workers to individuals with mental disorders in Africa. A systematic search was conducted in Scopus, Google Scholar, and PubMed for peer-reviewed articles published between 2000 and 2023. The risk of bias was assessed using QUADAS-2, while the Cultural Adaptation Assessment Tool (CAAT) was used to evaluate the cultural relevance of the interventions. Expert consultation followed Cochrane Handbook guidelines. Out of 13,201 records, ten studies from Uganda, Kenya, Zimbabwe, Ethiopia, the Democratic Republic of Congo, and South Africa met the inclusion criteria. These studies described eight intervention types, including group-based interpersonal psychotherapy (IPT), trauma-focused cognitive behavioral therapy (CBT), community trauma therapy, counseling, problem-solving therapy, peer support, task-shared care, and group support psychotherapy. The interventions targeted depression, anxiety, trauma, and suicidal behavior. All interventions were culturally adapted for delivery by community health professionals. Although study designs varied, resulting in differences in evidence quality, findings suggest these culturally relevant interventions are promising in meeting Africa’s mental health needs. Further research is needed to assess their effectiveness among adolescents, older adults, and individuals with severe mental disorders and self-harm behaviors.